IoT Prototype System of Flood Detection at Housing Pondok Gede - Fadhlam Bihamdi; Nurwijayanti KN (Politeknik Pertanian Negeri Samarinda, 2022)
Indonesia is a country with a tropical climate. Entering the rainy season, a number of areas along the river have the potential to be affected by flooding, especially the Pondok Gede Permai residential area. Flooding is a big problem for the affected community, it makes the surrounding community panic, because the flood comes suddenly without knowing the time, seeing conditions like this then a tool is made to give an early warning of the arrival of flooding from the river, so that the community around the Pondok housing complex is made. the big game is more alert to flooding. In the Industrial 4.0 era, the Internet of things has developed rapidly, so flood early warning tools take advantage of IoT technology. The purpose of this study is to provide a programmatic framework for flood early warning. The tool framework that will be created is in the form of an IoT-based programmatic flood location model. By utilizing the NodeMCU ESP8266 as a control, transistors as sensors to identify water levels, Flow meter sensors as water release seekers, LEDs and LCDs as pointers, Buzzer as the highest level warning and the Blynk Application to observe river water levels via Android phones so that the people of Pondok Gede Permai especially those near the riverbanks are already alert. The prototype design of this Automatic Flood Detection System produces information that is sent by the NodeMCU ESP8266 to the Blynk Application as an information receiver. an error rate of 7.85 percent with a time span of 4 minutes 3 seconds when the water reaches its highest level and has notifications set within the Blynk App.